Experimenting with Raspberry Pi - Gay, Warren W. (Springer, 2014)
Need some inspiration for your Raspberry Pi projects? Wondering how to work with Wii nunchucks, stepper motors, how to create a remote control panel? If you need guidance, Experimenting with Raspberry Pi is your own personal idea generator. Experimenting with Raspberry Pi covers how to work with various components and hardware like humidity and temperature sensors, Wii nunchucks, GPIO extenders, and IR receivers so you can add these to your own projects. Written with budgets in mind, author Warren Gay encourages you to build, experiment, and swap out various parts to learn more about the Pi and come up with the best ideas and instructions for your own amazing Raspberry Pi project ideas.
Vendor-supplied metadata
Keywords: Raspberry Pi (Computer); computerwetenschappen; computer sciences; operating systems; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen); Raspberry Pi (Ordinateur); COMPUTERS; Hardware; General